The role of macrophages-mediated communications among cell compositions of tumor microenvironment in cancer progression - Li, Mengyuan; Jiang, Ping; Wei, Shuhua; Wang, Junjie; Li, Chunxiao (Frontiers in Immunology, 2023)
Recent studies have revealed that tumor-associated macrophages are the most abundant stromal cells in the tumor microenvironment and play an important role in tumor initiation and progression. Furthermore, the proportion of macrophages in the tumor microenvironment is associated with the prognosis of patients with cancer. Tumor-associated macrophages can polarize into anti-tumorigenic phenotype (M1) and pro-tumorigenic phenotype (M2) by the stimulation of T-helper 1 and T-helper 2 cells respectively, and then exert opposite effects on tumor progression. Besides, there also is wide communication between tumor-associated macrophages and other immune compositions, such as cytotoxic T cells, regulatory T cells, cancer-associated fibroblasts, neutrophils and so on. Furthermore, the crosstalk between tumor-associated macrophages and other immune cells greatly influences tumor development and treatment outcomes. Notably, many functional molecules and signaling pathways have been found to participate in the interactions between tumor-associated macrophages and other immune cells and can be targeted to regulate tumor progression. Therefore, regulating these interactions and CAR-M therapy are considered to be novel immunotherapeutic pathways for the treatment of malignant tumors. In this review, we summarized the interactions between tumor-associated macrophages and other immune compositions in the tumor microenvironment and the underlying molecular mechanisms and analyzed the possibility to block or eradicate cancer by regulating tumor-associated macrophage-related tumor immune microenvironment.